Polo industrial ecológico de Manaus: uma proposta para o alcance da sustentabilidade - Branco, Roderick Cabral Castello (2009)
The present study has as its central objective verify what are the main changes that the Manaus Industrial Park must go through in order to be considered and Eco-Industrial Park (EIP), an Industrial Ecology s (EI) tool committed with the achievement of Sustainable Development. The social and economic importance that the Manaus Industrial Park has to the city, along with the environmental matter s visibility in the Amazonian region, shows the relevance of this study in helping the search for sustainable alternatives to the industry in the Amazon, with benefits to everyone involved with the industrial park. About the theoretical foundation of this research, it is divided into three distinct stages. A first, a dense survey of the literature in concern about Sustainable Development, IE and EIP is done, marking this work s theoretical foundation. Then, the city of Manaus and its industrial park are described into their social and economic aspects, providing the necessary elements for the understanding of local reality. In a third stage, in order to achieve this dissertation s main objective, the comparison between the distinguishing features of the PIE s concept, as shown in the international literature, and those observed at the Manaus Industrial Park, obtained by visiting twenty different enterprises that represent the whole industrial park, is made. To do so, directors and/or social and environmental managers have been interviewed. From this comparison, this study revealed several initiatives found in the concept of EIP that are not present in the surveyed companies. The results were organized according to the triad of sustainability, duo to the connection between these two concepts, making it possible to observe that: considering the environmental pillar, it was found that the measures adopted by the surveyed companies are, actually, previous stages to those observed in eco-industrial systems; in the social pillar, despite the existence of several initiatives, corporate social actions ignore those focused in the development of community businesses a strongly suggested characteristic by the literature; finally, in the economic pillar, its argued that the industrial park has competitive attributes to guarantee the survival and prosperity of business (yet local economy is still dependent on a policy of tax incentives). Although far from the ideal concept shown in the EIP literature, the comparison helps to understand the shortcomings of the current model, serving, possibly, as a direction of movements concerned with a just and environmentally responsible future while promoting a competitive advantage for companies associated